Process-Aware Systems First International Workshop, PAS 2014, Shanghai, China, October 17, 2014. Proceedings - Cao, Jian.; Cao, Jian.; Wen, Lijie.; Wen, Lijie.; Liu, Xiao.; Liu, Xiao. (Communications in Computer and Information Science,, 2015)
This book constitutes the refereed proceedings of the First International Workshop on Process-Aware Systems, PAS 2014, held in Shanghai, China, in October 2014. The 5 revised full papers and 3 short papers were carefully reviewed and selected from 14 submissions. The papers are organized in topical sections on process modeling and comparison; workflow scheduling and resource allocation; scientific workflow verification; workflow applications.